Implementasi Program Keterampilan Hidup dalam Kurikulum Pendidikan Agama Islam : Implementation of Life Skills Program in Islamic Religious Education Curriculum - Robiyah, Anis Saatul; Bakri, Syamsul (STAI Publisistik Thawalib Jakarta, 2024)
Life skills in Islamic Education help students tackle life's challenges through knowledge, attitudes, and vocational skills that support moral development in accordance with Islamic teachings. This research analyzes the implementation of the Life Skills Program in the Islamic Education curriculum at Kasatria Vocational School in Solo Sukoharjo using a qualitative approach and phenomenological study. Data were collected through observations, interviews, and documentation, then processed through reduction, presentation, and conclusion drawing, with data validity ensured through triangulation. The findings indicate that life skills are integrated into annual and semester programs, focusing on essential and personal skills. Interactive learning aids students in facing daily challenges and enhancing their self-potential. Individual skills include self-awareness and decision-making abilities. Work readiness skills teach discipline and hard work, which are vital for the job market. Skills training inspires reasoning abilities, while cooperative exercises enable students to present and discuss materials, building communication and collaboration skills that prepare them to work effectively in teams.